Bank digitalization and corporate green innovation: empowering or negative? - Jia, Kaiwei; Zhang, Yu (Frontiers in Energy Research, 2024)
In the context of bank digitalization construction, this paper explores the impact and mechanism of bank digital transformation on corporate green innovation based on the data of listed enterprises from 2010 to 2021. It is found that bank digital transformation enhances the overall and strategic nature of corporate green innovation but has no significant impact on corporate substantive green innovation. The mechanism analysis shows that bank digital transformation can promote corporate green innovation by inhibiting corporate financialization and alleviating corporate financing constraints. Government environmental regulation and media attention have a positive moderating effect on the relationship between banks’ digital transformation, and enterprises’ green innovation, i.e., an increase in the level of government environmental regulation and an increase in media attention will strengthen the promotion effect of banks’ digital transformation on enterprises’ green innovation. Heterogeneity analysis shows that the promotion effect of banks’ digital transformation on corporate green innovation is more significant for state-owned enterprises, heavily polluted enterprises, large-scale enterprises, and enterprises in the eastern region. Therefore, the digital transformation of banks can “empower” the green innovation of enterprises, help the green development of enterprises, and lead the high-quality development of the economy. At the same time, the study’s results also show that the green development of enterprises should not be “superficial” but “substantial.”